A comparative study on nosocomial and community-acquired bacterial urinary tract infections: prevalence, antimicrobial susceptibility pattern, and associated risk factors among symptomatic patients attending Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia - Fekadu, Sisay; Weldegebreal, Fitsum; Shumie, Tadesse; Mekonnen, Getachew Kabew (Frontiers in Epidemiology, 2025)
BackgroundUrinary tract infections (UTIs) remain one of the most common diseases worldwide that occur both in the community and in healthcare settings. Thus, this study aimed to compare the burden of nosocomial and community-acquired bacterial UTIs among patients attending Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia.MethodA hospital-based cross-sectional study was conducted using a convenient sampling technique from January 2024 to April 2024. Descriptive statistics were employed, and bivariate and multivariable logistic regression analyses were used to identify associated factors at p < 0.05 with a 95% confidence interval (CI) considered statistically significant.ResultsThe rate of hospital-acquired UTIs was 42% (95% CI: 35–50), while the rate of community-acquired UTIs was 28% (95% CI: 22–36). The predominant bacterial isolates were Escherichia coli (37%), Staphylococcus aureus (7.8%), and Klebsiella pneumoniae (7.8%). The overall multidrug resistance rate was 91 (77.8%). Lack of formal education [adjusted odds ratio (AOR), 0.02; 95% CI: 0.001–0.6], surgery during admission (AOR, 0.02; 95% CI: 0.002–0.3), delay in voiding urine (AOR, 0.01; 95% CI: 0.005–0.1), previous UTIs (AOR, 0.04; 95% CI: 0.004–0.4), and previous admission (AOR, 0.07; 95% CI: 0.01–0.5) were the main factors significantly associated with bacterial UTIs.ConclusionsA significantly higher prevalence of hospital-acquired bacterial UTIs was observed compared to community-acquired bacterial UTIs. The commonest isolates were E.coli, S. aureus, and K. pneumoniae. The drug resistance rate was very high. Modifiable individual-level factors were the major significant factors of UTIs. Thus, health workers and other stakeholders should tackle UTIs by increasing community awareness, promoting personal hygiene, and improving healthcare service quality.